2008
DOI: 10.1002/anie.200705079
|View full text |Cite
|
Sign up to set email alerts
|

Surface Synthesis of 2D Branched Polymer Nanostructures

Abstract: Molecular nanostructures formed by bottom-up self-organization [1] are model systems for advanced functional surfaces with a broad range of applications, such as sensors or coatings, molecular electronics, and heterogeneous catalysis. Supramolecular structures formed on surfaces under ultrahighvacuum (UHV) conditions through exploitation of noncovalent interactions, such as van der Waals forces, [2] dipole-dipole interactions, [3] hydrogen bonding, [4] or metal complexation, [5] have been studied extensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
130
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(133 citation statements)
references
References 48 publications
0
130
0
3
Order By: Relevance
“…A strategy to overcome this low stabilization energy relies on inducing covalent reactions between the molecular components, thus forming twodimensional covalently bonded networks. The formation of covalent bonds between complementary molecular components is an appealing approach in the fabrication of nanoscale structures, such as nanomeshes and nanolines, because of their high selectivity, strength, and directionality [3,[14][15][16][17][18][19][20][21][22][23][24][25][26]. These nanostructures are attractive for their intrinsic properties; for their potential applications such as in novel sensing, energy conversion or catalytic devices; for their ability to "trap" other molecules such as fullerenes, creating even more interesting complexes and for their use as templates to direct the growth of, for example, metal clusters with interesting catalytic or magnetic properties [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…A strategy to overcome this low stabilization energy relies on inducing covalent reactions between the molecular components, thus forming twodimensional covalently bonded networks. The formation of covalent bonds between complementary molecular components is an appealing approach in the fabrication of nanoscale structures, such as nanomeshes and nanolines, because of their high selectivity, strength, and directionality [3,[14][15][16][17][18][19][20][21][22][23][24][25][26]. These nanostructures are attractive for their intrinsic properties; for their potential applications such as in novel sensing, energy conversion or catalytic devices; for their ability to "trap" other molecules such as fullerenes, creating even more interesting complexes and for their use as templates to direct the growth of, for example, metal clusters with interesting catalytic or magnetic properties [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42] The Schiff base reaction has been widely applied in dynamic covalent chemistry, [43,44] and it has also been investigated both under UHV and ambient conditions by means of scanning tunneling microscopy (STM). [23][24][25][32][33][34][35] The reactions, particularly those that result in small-molecule imine compounds, can proceed under room temperature, [32,43] whereas for the preparation of high-quality surface 2D polymers, mild heating is normally necessary. An in-depth understanding of the mechanism of the surface-confined reaction-for instance, the effect of monomer diffusion, polarity of the solvent, and so forth-is crucial for improving the quality and properties of the obtained nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that the number and position of reactive groups, and the symmetry and rigidity of backbones of the precursors play important roles in the resultant structures and morphologies. For instance, selecting proper reactive components can fabricate 1D or branched polymers, [25,[30][31][32][33][34] 2D chiral architectures, [35] and networks with different periods and pore sizes. [21,24] Highly or-dered large-scale 2D surface covalent organic frameworks (COFs) on highly oriented pyrolytic graphite (HOPG) have also been prepared by means of a self-limiting solid-vapor interface reaction method, mild heating under open or closed environments, [36,37] or even by reaction at the solid-liquid interface at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Recently, a huge number of works have been done for their potential application on biomedicine and catalysis. [4][5][6] The syntheses of the branched or hyperbranched polymers are still an attracting topic today. The radical solution copolymerization of a vinyl monomer with a divinyl monomer is one of the simple routes.…”
Section: Introductionmentioning
confidence: 99%